2008
DOI: 10.1021/jp804135e
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lived Radical Cations as Model Compounds for the Reactive One-Electron Oxidation Product of Vitamin E

Abstract: Heterocyclic compounds with structures similar to vitamin E, but without the hydroxyl hydrogen atom, were synthesized and their electrochemical behavior examined in acetonitrile solutions and as solids in aqueous solutions of varying pH by attaching the compounds to the surface of a glassy carbon electrode. Compound 1, containing a fully methylated aromatic ring was found to be the most long-lived following one-electron oxidation, with its radical cation (1 +• ) surviving in acidic aqueous solutions and able t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…In this case D@50 (with peaks located at approximately 314 and 490 nm) can be identified with S d on account of its similarity to the spectrum of the radical cation of an analogue of EOH in which the phenolic H-atom is lacking; this cation, generated electrochemically in acetonitrile, displayed peaks at 313 and 482 nm. 25 Our assignment is also consistent with the crucial result, to be presented below, that TOMe + is able to donate its hole to C. On this basis D@1 can be immediately interpreted as the superposition of S e and S d ; in N 2 O-saturated solutions, only S d is observed.…”
Section: Resultssupporting
confidence: 90%
“…In this case D@50 (with peaks located at approximately 314 and 490 nm) can be identified with S d on account of its similarity to the spectrum of the radical cation of an analogue of EOH in which the phenolic H-atom is lacking; this cation, generated electrochemically in acetonitrile, displayed peaks at 313 and 482 nm. 25 Our assignment is also consistent with the crucial result, to be presented below, that TOMe + is able to donate its hole to C. On this basis D@1 can be immediately interpreted as the superposition of S e and S d ; in N 2 O-saturated solutions, only S d is observed.…”
Section: Resultssupporting
confidence: 90%
“…5 (1.0-1.7 m) sintered glass frit [24]. The working and auxiliary electrodes used were two identically sized Pt mesh plates both symmetrically arranged with respect to each other with an Ag wire reference electrode (isolated from the working electrode compartment by a salt bridge) positioned to within 2 mm of the surface of the working electrode.…”
Section: Electrochemical Proceduresmentioning
confidence: 99%
“…The existing experiments performed on R-TOH have indicated that electrochemical oxidation in the dry organic solvents (CH 3 CN or CH 2 Cl 2 ) results in the formation of R-TO þ as a long-lived species, 55,[59][60][61][62][63][64][65][66] while oxidation of R-TOH in the presence of water results in the rapid (and chemically irreversible) formation of R-TOQ. 58,67 An important question relates to the potential oxidation pathway of R-TOH in a bilayer membrane environment similar to where it exists biologically, and whether any of the cationic species shown in Scheme 1 can have an appreciable lifetime.…”
Section: R-toh -2ementioning
confidence: 99%
“…Using this procedure, it is not critical for the electrode to be perfectly coated, since any pinholes or defects will only incorporate the electrolyte ions, whereas the electroactive molecules will remain completely encapsulated within the membrane structure. The molecules α-tocopherol (vitamin E) and vitamin K 1 that exist naturally within lipid bilayer membranes were chosen to examine because they undergo redox reactions as part of their modus operandi and there exists extensive literature reports of the voltammetric properties of these molecules both in organic solvents , ,, and as oils attached to electrodes in aqueous solutions. ,− …”
Section: Introductionmentioning
confidence: 99%